Analysis of Tourist Perceptions of Ecotourism Facilities in Surabaya Mangrove Forest - Rachmad Kodariawan; Samsul Huda; Sri Tjondro Winarno; Hamidah Hendrarini (Postgraduate, University of Mataram, 2025)
Mangrove ecotourism has been increasingly developed as both a tourist destination and a conservation medium; however, understanding of visitor perceptions toward available facilities remains limited. This study aims to identify tourist evaluations of mangrove forest ecotourism in Surabaya by examining four dimensions: accessibility, attractions, supporting infrastructure, and additional services. A survey was conducted with 100 respondents at Wonorejo, Medokan, and Gunung Anyar mangrove sites, and the data were analyzed using WarpPLS 8.0 to test the validity and reliability of the instruments. The results indicated that all indicators were consistent, and overall tourist assessments tended to be positive. The main strengths were the well-preserved environment, integration of local culture, and staff hospitality, while entertainment attractions were perceived as less developed. These findings highlight the importance for managers to maintain the existing strengths while improving weaker aspects in order to provide a more comprehensive visitor experience. An integrated enhancement of facilities is considered essential to strengthen visitor satisfaction and improve destination competitiveness. From an academic perspective, this study contributes as a reference for future research on mangrove ecotourism and tourism development studies.